2017
DOI: 10.1007/s13205-017-0784-8
|View full text |Cite
|
Sign up to set email alerts
|

Species specific PCR based detection of Escherichia coli from Indian foods

Abstract: Escherichia coli is a faecal indicator and certain virotypes are known as pathogens. Therefore, detection and prevention of E. coli in food is very important. The existing rapid methods concentrate on detecting the pathogenic E. coli instead of total E. coli population. Present study evaluates the use of two molecular markers (uidA and flanking region of uspA) specific for the E. coli in combination with microbiological method for confirmation. Majority of the isolates (77%) were positive for both the genes te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 22 publications
1
26
0
Order By: Relevance
“…Lactose-positive, red, non-mucoid colonies were randomly selected from each sample and sub cultured onto Eosin Methylene Blue agar (EMB) (Scharlau, Spain) for biochemical confirmation. Species identity of E. coli was confirmed by standard biochemical properties followed by species-specific multiplex PCR 57 . Primers for the uidA gene and flanking region of the uspA gene were used.…”
Section: Methodsmentioning
confidence: 99%
“…Lactose-positive, red, non-mucoid colonies were randomly selected from each sample and sub cultured onto Eosin Methylene Blue agar (EMB) (Scharlau, Spain) for biochemical confirmation. Species identity of E. coli was confirmed by standard biochemical properties followed by species-specific multiplex PCR 57 . Primers for the uidA gene and flanking region of the uspA gene were used.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 18 isolates (31.5%) from the cloacal swabs, litter, and drinking water samples were positive for the presence of the flanking regions uspA gene (Figure -1). The uspA gene has been used as a DNA marker for the identification of E. coli by Chen & Griffiths (1998), and it is considered by another study (Godambe et al, 2017). Another report about the prevalence of E. coli in poultry from Egypt showed that 35% of the samples were positive for E. coli (Amer et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, mycobacteria are renowned etiological agents of disease as has already been discussed. The uidA gene, on the hand, is a known molecular marker gene used to identify pathogenic Escherichia coli (Feng and Lampel 1994;Godambe et al 2017).…”
Section: Discussionmentioning
confidence: 99%